Local complication after radial artery harvest to coronary artery bypass grafting - Drohomirecka, Anna; Cichoń, Romuald (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2012)
Nowadays there is an increasing trend to use arterial grafts in surgical coronary revascularization. The radial artery is one of the grafts used in this type of operation. Harvesting the radial artery may potentially reduce the operated forearm and hand function. The paper is a systematic review of literature concerning the local complications (disturbances of sensation, motor and fine function of the upper extremity) after removal of the radial artery for coronary artery bypass grafting.